ANALISIS PENGARUH PENERAPAN ERP DALAM MENINGKATKAN KINERJA SUPPLY CHAIN MANAGEMENT PADA PT INDOFOOD CBP SUKSES MAKMUR Tbk. - Ong, Teddy; Qadri, Rizni Aulia; Verandi, Rizal; Elida, Shelly E; Christy, Angelica Vivian (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
PT. Indofood is one of the largest food product manufacturing companies inIndonesia. This article discusses the ERP system used by PT. Indofood to improvetheir supply chain management performance as well as their operationalperformance. The method used in this study is qualitative, in which the data issought from valid sources and references and has been studied previously. Theresult of this research is the ERP system used by PT. Indofood can improveoperational performance as well as performance of existing supply chainmanagement.Keyword: ERP System, Foods, Indofood, Supply Chain Management